Active listening techniques 30 practical tools to hone your communication skills - Leonardo, Nixaly (Tantor Media, Inc., 2022)
To listen actively is to listen with complete attention and an engaged mind and body. And, while it may come naturally to some, it's also a skill that can be honed through practice. Active Listening Techniques will help you do just that, so you can ensure the people around you feel respected, understood, and heard. Through thirty practical communication tools, you'll acquire the skills you need to better get your message across, allowing you to cultivate healthier personal relationships, achieve greater career success, and more. This guide to listening skills for adults helps you: - Learn the basics-Discover the importance of paraphrasing, nonverbal cues, emotional labeling, mirroring, validation, and other fundamental techniques. - Put your skills to use-Each communication tool includes an illustrative anecdote, as well as digestible strategies to help you apply the concept to your everyday life. - Manage conflict-Learn how invaluable being an active listener is when it comes to navigating difficult or emotionally charged situations. Learn how to develop stronger connections through these simple and effective listening exercises.
Keywords: Listening; Communication; Active learning; Écoute (Psychologie); Apprentissage par l'action; Information